The Effect of Health Service Quality and Brand Image on Patients Loyalty, With Patients Satisfaction as Mediating Variable (A Study in Vip Ward Of Prof. Dr R Soeharso Ortopedics Hospital In Surakarta) - Tangkas Sibarani; Asri Laksmi Riani (Universitas Sebelas Maret, 2017)
Business in healthcare service, like other service business, should provide a service to its patients in order to maintain patients’ loyalty to be a loyal customer. A method in increasing patients’ satisfaction and loyalty is by focusing a hospital’s business on service quality aspect. Customers’ satisfaction is an effective measurement in assessing service quality that is based on patient’s consideration on the service provided and their personal experience. The main objective of this research is to understand the effect of service quality and brand image on patients’ loyalty, with patients’ satisfaction as mediating variable. To determine the determinant of patients’ satisfaction, the study is focused on the inpatients, especially those who stay at VIP ward, of Prof Dr R Soeharso Ortopedics Hospital Surakarta, Central Java, Indonesia. The research method used is survey, which is conducted by distributing a questionnaire directly to the surveyed patients. Reliability and validity test (using Servqual instrument) is conducted. The respondents of this research consist of 211 inpatients. The data collected is analyzed using SEM method. The result shows that service quality affects patients’ satisfaction through brand image and service quality. Simultaneously, service quality and brand quality affect patients’ satisfaction. Therefore, patients’ satisfaction affects patients’ loyalty. The implication of this research is the manager of a health care company should continuously improve the service quality and brand image, thus increasing patients’ satisfaction, which will lead to patients’ loyalty.